If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -3) + 9x = 0 Reorder the terms: 2(-3 + x) + 9x = 0 (-3 * 2 + x * 2) + 9x = 0 (-6 + 2x) + 9x = 0 Combine like terms: 2x + 9x = 11x -6 + 11x = 0 Solving -6 + 11x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 11x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 11x = 0 + 6 11x = 0 + 6 Combine like terms: 0 + 6 = 6 11x = 6 Divide each side by '11'. x = 0.5454545455 Simplifying x = 0.5454545455
| (x+4)(x+4)+5=86 | | 2+5x=-10x | | 4x-7x-73=81 | | 2+5x=-10 | | 6x=-31 | | 5x-70=4x+20 | | 924x^6/2x^12 | | -3(x+6)=4(x-1) | | 6.5=6.28r | | .5x+.025= | | -10x-x-93=149 | | (4x-2)(5x-5)=x | | 6(6t-5)+t=60-t | | 6[6-(-9x-4)]=378x+204 | | 8+2m-6=9m+5-6m | | 7x+5=23+4x | | X^2=40+x | | 15+x^3=5x^3-17 | | (5x-7x)(6y)= | | -2x+6x-76=44 | | h(t)=-16t^2+12fort | | -5.2(x-3.25)=20.8 | | 3(r+79)=-27 | | y=1/5(-15)-5 | | f=9/5(191.8-273.15)-32 | | a+9=-4 | | 2x+24=9+5x | | 4.8(x-3.75)=14.4 | | .5(x+.05)= | | 6+7y=69 | | g-2=-46 | | 8-4k=12 |